Olfactory Dysfunction as a Clinical Marker of Early Glymphatic Failure in Neurodegenerative Diseases - Gonzalo Sánchez-Benavides; Alex Iranzo; Oriol Grau-Rivera; Darly Milena Giraldo; Mariateresa Buongiorno (Diagnostics)
An abnormal accumulation of misfolded proteins is a common feature shared by most neurodegenerative disorders. Olfactory dysfunction (OD) is common in the elderly population and is present in 90% of patients with Alzheimer’s or Parkinson’s disease, usually preceding the cognitive and motor symptoms onset by several years. Early Aβ, tau, and α-synuclein protein aggregates deposit in brain structures involved in odor processing (olfactory bulb and tract, piriform cortex, amygdala, entorhinal cortex, and hippocampus) and seem to underly OD. The glymphatic system is a glial-associated fluid transport system that facilitates the movement of brain fluids and removes brain waste during specific sleep stages. Notably, the glymphatic system became less functional in aging and it is impaired in several conditions, including neurodegenerative diseases. As the nasal pathway has been recently described as the main outflow exit of cerebrospinal fluid and solutes, we hypothesized that OD may indeed be a clinical marker of early glymphatic dysfunction through abnormal accumulation of pathological proteins in olfactory structures. This effect may be more pronounced in peri- and postmenopausal women due to the well-documented impact of estrogen loss on the locus coeruleus, which may disrupt multiple mechanisms involved in glymphatic clearance. If this hypothesis is confirmed, olfactory dysfunction might be considered as a clinical proxy of glymphatic failure in neurodegenerative diseases.